The Effect of Audit Quality, Tax Avoidance, Leverage, and Presentation of Other Comprehensive Income on Firm’s Value in Jakarta Islamic Index Company - Kalbuana, Nawang; Yohana; Agustina; Ranny Cynthia Aryadi (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
The purpose of this research is to analyze the influence of Audit Quality, Tax Avoidance, Leverage, and presentation of Other comprehensive Income on Firm’s Value in companies listed in the Jakarta Islamic Index (JII) during 2015-2019. In this study Firm’s Value reflects the current value of future desired earnings and an indicator for the market in assessing the company as a whole. The sample is selected by purposive sampling method. While hypothetical testing uses multiple linear regression analysis methods. The results of this study show that variable Quality Audit, Tax Avoidance and presentation of Other comprehensive Income, have no significant effect on Firm’s Value, while Leverage has a significant effect on Firm’s Value. Simultaneously it is suggested that the Quality of Audit, Tax Avoidance, Leverage, and presentation of Other comprehensive Income has no significant effect. The implications of this research are expected to contribute theoretically to the value of Islamic companies and practically provide input for policy makers and regulators in the Jakarta Islamic Index.